Transforming Education in the Age of Artificial Intelligence: Challenges and Opportunities in Indonesia, A Literature Review - Rakuasa, Heinrich; Dzaka Ashriel Faris; Muh. Hidayatullah (Yayasan Perguruan Kampus, 2024)
In the era of artificial intelligence, education transformation in Indonesia faces significant challenges and opportunities. Key challenges involve disparities in technology access between regions, curriculum adjustments, and teachers' lack of understanding of artificial intelligence. Meanwhile, opportunities include the potential for personalized learning, responsive curriculum development, and the use of artificial intelligence in learning monitoring. With these dynamics in mind, the transformation of education in Indonesia is not only a response to challenges, but also an opportunity to create a more inclusive and technologically relevant education system. This research uses a descriptive qualitative approach using the literature study method. The results of this study discuss the challenges and opportunities of education in the era of artificial intelligence and strategies for implementing educational transformation. The results show that this educational transformation not only offers an opportunity to update the education system, but also to create a learning environment that is more inclusive and relevant to future needs. With the right implementation strategy, Indonesia can optimize the potential of artificial intelligence in improving the quality and accessibility of education across the country.